Do research participants share genomic screening results with family members?. Issue 2 (19th October 2021) - Wynn, Julia; Milo Rasouly, Hila; Vasquez‐Loarte, Tania; Saami, Akilan M.; Weiss, Robyn; Ziniel, Sonja I.; Appelbaum, Paul S.; Wright Clayton, Ellen; Christensen, Kurt D.; Fasel, David; Green, Robert C.; Hain, Heather S.; et al.
Abstract: The public health impact of genomic screening can be enhanced by cascade testing. However, cascade testing depends on communication of results to family members. While the barriers and facilitators of family communication have been researched following clinical genetic testing, the factors impacting the dissemination of genomic screening results are unknown. Using the pragmatic Electronic Medical Records and Genomics Network‐3 (eMERGE‐3) study, we explored the reported sharing practices of participants who underwent genomic screening across the United States. Six eMERGE‐3 sites returned genomic screening results for mostly dominant medically actionable disorders and surveyed adult participants regarding communication of results with first‐degree relatives. Across the sites, 279 participants completed a 1‐month and/or 6‐month post‐results survey. By 6 months, only 34% of the 156 respondents shared their results with all first‐degree relatives and 4% did not share with any. Over a third (39%) first‐degree relatives were not notified of the results. Half (53%) of participants who received their results from a genetics provider shared them with all first‐degree relatives compared with 11% of participants who received their results from a non‐genetics provider. The most frequent reasons for sharing were a feeling of obligation (72%) and that the information could help family members make medical decisions (72%). The most common reasons indicated for not sharing were that the family members were too young (38%), or they were not in contact (25%) or not close to them (25%). These data indicate that the professional returning the results may impact sharing patterns, suggesting that there is a need to continue to educate healthcare providers regarding approaches to facilitate sharing of genetic results within families. Finally, these data suggest that interventions to increase sharing may be universally effective regardless of the origin of the genetic result.